The rise of internet of things and big data on the cloud: challenges and future trends - Laouratou, Diallo; Hassan Abdalla Hashim, Aisha; Salami, Momoh Jimoh Eyiomika; Sara Babiker, Omer Elagib; Abdullah, Ahmad Zarir (Science and Engineering Research Support Society, 2017)
Huge growth in the scale of data generated through cloud computing has been led to Internet of Things (IoT). Fog computing has been recently adopted to improve some features of cloud computing and makes cloud computing more attractive to users. Furthermore, it comes to improve some parameters such as latency, security and load network. The combination of cloud and fog computing is seen a new progress in distributed computing and the appropriate platform for the data. Fog computing is defined as a new paradigm that works at the edge of the network to improve the quality of the network. In this paper, the use of fog computing in cloud computing is reviewed in this work. The characteristics, architectures and discussions and the relationship is further elaborated. Additionality, recommendation for further research is discussed.